2021
DOI: 10.3390/antibiotics10070824
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry and Ginger Silver Nanoparticles as Potential Inhibitors for SARS-CoV-2 Assisted by In Silico Modeling and Metabolic Profiling

Abstract: SARS-CoV-2 (COVID-19), a novel coronavirus causing life-threatening pneumonia, caused a pandemic starting in 2019 and caused unprecedented economic and health crises all over the globe. This requires the rapid discovery of anti-SARS-CoV-2 drug candidates to overcome this life-threatening pandemic. Strawberry (Fragaria ananassa Duch.) and ginger (Zingiber officinale) methanolic extracts were used for silver nanoparticle (AgNPs) synthesis to explore their SARS-CoV-2 inhibitory potential. Moreover, an in silico s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 68 publications
(99 reference statements)
1
28
0
Order By: Relevance
“…Green silver NPs prepared with silver nitrate and methanolic extracts of strawberry (Fragaria ananassa Duch.) or ginger (Zingiber officinale Roscoe) have been reported for their strong anti-viral activity against SARS-CoV-2, a finding in agreement with binding of the common phytochemical neohesperidin with both human AAK1 (AP2 associated kinase 1) protein and SARS-CoV-2 NSP16 protein [316]. Green silver NPs prepared with silver nitrate and Curcuma longa L. (Zingiberaceae) tuber powder extracts have been mentioned as being of potential use for biomedical purposes [317]; notably, curcumin, a polyphenolic phytochemical ((1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione), also called diferuloylmethane) found in Curcuma longa tubers, is regarded as a potential treatment for COVID-19 [318].…”
Section: Nanoparticlessupporting
confidence: 62%
“…Green silver NPs prepared with silver nitrate and methanolic extracts of strawberry (Fragaria ananassa Duch.) or ginger (Zingiber officinale Roscoe) have been reported for their strong anti-viral activity against SARS-CoV-2, a finding in agreement with binding of the common phytochemical neohesperidin with both human AAK1 (AP2 associated kinase 1) protein and SARS-CoV-2 NSP16 protein [316]. Green silver NPs prepared with silver nitrate and Curcuma longa L. (Zingiberaceae) tuber powder extracts have been mentioned as being of potential use for biomedical purposes [317]; notably, curcumin, a polyphenolic phytochemical ((1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione), also called diferuloylmethane) found in Curcuma longa tubers, is regarded as a potential treatment for COVID-19 [318].…”
Section: Nanoparticlessupporting
confidence: 62%
“…Jeremiah et al evaluated AgNPs with different sizes and concentrations and found that 1–10 ppm of the particles with a diameter of approximately 10 nm could effectively neutralize extracellular SARS-CoV-2, and cytotoxicity was observed at >20 ppm [ 19 ]. Al-Sanea et al applied strawberry and ginger extracts in the fabrication of AgNPs, to enable the anti-SARS-CoV-2 activity [ 38 ]. Surface modification of AgNPs can significantly affect their biocompatibility and their interaction with cells [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further evaluate the antiviral activity, in silico molecular docking study was conducted to examine the potential phytochemicals that might bind to and inhibit SARS-CoV-2 proteins. Among 30 compounds, neohesperidin showed better binding affinity to SARS-CoV-2 NSP16 protein (Al-Sanea et al, 2021).…”
Section: In Silico Study On Sars-cov-2mentioning
confidence: 99%